Sublingual immunotherapy dosing regimens: What is ideal? - Jin, Jay J.; Pfaar, Oliver (The journal of allergy and clinical immunology. In practice, 2017)
Sublingual immunotherapy (SLIT) is a treatment for allergic respiratory diseases that has demonstrated efficacy and safety. Several formulations of SLIT are now available worldwide for treatment of allergic rhinitis (AR). Grass tablets containing 15 to 25 μg of group 5 major allergen reduced combined AR symptoms and medication use by 23% to 41% in 3 treatment years and 2 follow-up years. Ragweed pollen tablets (12 μg of Ambrosia artemisiifolia 1) and liquid extracts (50 μg of Ambrosia artemisiifolia 1) reduced combined AR symptoms and medication use by 26% and 43%, respectively. House dust mite tablets containing 300 index of reactivity (16 μg of Dermatophagoides pteronyssinus 1 and 68 μg of Dermatophagoides farinae 1) reduced AR symptoms by 17.9% and 17.0% in 1 treatment year and 1 follow-up year, respectively. A different house dust mite tablet (12 standardized quality house dust mite) was able to reduce the risk of asthma exacerbation compared with placebo (hazard ratio, 0.69; 95% CI, 0.50-0.96). Most adverse events were local and mild to moderate in severity. For SLIT products reviewed herein, effective doses range from 1.12 to 84 μg of major allergen(s). However, allergen content is not uniformly standardized, can be expressed in arbitrary or proprietary units (depending on the manufacturer), and assays for determination of allergen content are highly variable. Thus, results from one study of a given product cannot be extrapolated to other products. Despite these limitations, this Clinical Management Review aims to provide practitioners with relevant information on the dosing of selected SLIT formulations in the treatment of allergic respiratory disease.